Wide bandgap copolymers with vertical benzodithiophene dicarboxylate for high-performance polymer solar cells with an efficiency up to 7.49%. Issue 48 (17th November 2016) - Tao, Qiang; Liu, Tao; Duan, Linrui; Cai, Yufeng; Xiong, Wenjing; Wang, Pu; Tan, Hua; Lei, Gangtie; Pei, Yong; Zhu, Weiguo; Yang, Renqiang; Sun, Yanming
Abstract : A novel vertical carboxylate functionalized benzodithiophene unit was designed as an election-accepting block to build D–A type copolymers, and a high V oc of 1.03 V and a significant PCE of 7.49% were achieved. Abstract : In aiming to build novel wide band-gap high-performance photovoltaic donor materials, a vertical benzo[1, 2- b :4, 5- b ′]dithiophene-2, 6-dicarboxylate (V-BDTC) with a weak electron-withdrawing character was primarily developed. And its wide band-gap (WBG) copolymersPV-BDTC1 andPV-BDTC2 were designed and synthesized, which contain a traditional electron-donating unit of 4, 8-disubstituted benzo[1, 2- b :4, 5- b ′] dithiophene (BDT) derivative with diethylhexyloxy for the former and diethylhexylthiophenyl for the latter. It is found that the weak electron-withdrawing V-BDTC unit endows its copolymers with a WBG up to 2.09 eV and a deep HOMO energy level of ∼5.67 eV. Furthermore, PV-BDTC2 exhibits much better photovoltaic properties thanPV-BDTC1 in the solution-processing polymer solar cells (PSCs) with a higher open-circuit voltage ( V oc ) of 1.03 V and an increased power conversion efficiency (PCE) of 7.49%. To the best of our knowledge, this PCE value is the highest level recorded for copolymers with a WBG over 2.0 eV in the PSCs to date, along with a remarkable V oc over 1.0 V. This work provides a feasible strategy to develop a novel promising electron-withdrawing building block and its high-performance WBG copolymers based on the BDT unit.